Perlindungan Konsumen Terhadap Keamanan Pangan yang Dalam Proses Produksinya Menggunakan Pewarna Pakaian (Rhodamin B) - Kevin Birul Walidaini (Private Law Department, Faculty of Law, University of Jember, Indonesia, 2023)
Rhodamine B is one of the synthetic dyes commonly used in the textile and paper industry. Rhodamine B is often misused as a food coloring, especially in snacks. In fact, the government has stipulated Regulation of the Minister of Health of the Republic of Indonesia Number 722/Men.Kes/Per/VI/88 so as not to use Rhodamine as a food mixture. Even though there has been a ban, there are still many manufacturers that use rhodamine B in their food products. In the case found by the Food and Drug Supervisory Agency, there were still 12 out of 25 snacks that were positive for the synthetic dye Rhodamin B. After being investigated, it turned out that business actors still did not understand the regulations set by the government. This has led to several incidents of poisonings due to consuming food products containing hazardous chemicals, especially Rhodamine B. However, not all business actors do not understand the regulations made by the government, there are those who understand but still violate these regulations. Business actors who violate these regulations will of course be responsible for their actions to consumers who have suffered losses due to consuming these food products. Keywords: Rhodamine B, Food and Drug Supervisory Agency